Matrix method for balancing chemical equations of few ‎significant inorganic reactions - Sharma, Gitalee; Bhattacharyya, Surashmi; Bora, Niranjan (International Journal of Basic and Applied Sciences, 2025)
Balancing chemical equations provides a unified framework on understanding and quantifying chemical reactions, making it a fundamental ‎tool in chemistry. The prime objectives to balanced chemical equations are to make both sides of the reaction, the reactants as well as the ‎products, possess the same number of atoms per element. It is worth mentioning that understanding how and in what amounts certain mole-‎cules are created is made easier with the use of chemical reactions. It also indicates the quantity of reactants required to complete the reaction. ‎These two identities of a chemical reaction are specified by balancing the reaction, which also helps in understanding how to speed up or ‎stop the process. However, balancing long chemical reactions is a difficult and time-consuming task. Employing the principles of mathemat‎ical computation to the balancing of chemical equations may come as a remedy to this problem. Thus, in the current paper, we use a matrix-‎based method, Gauss Elimination mathematical model to balance the chemical equations of a few specific inorganic reactions. Computation ‎work was performed and validated with the help of Python software‎.
Keywords: Augmented Matrix; Chemical Equations; Gauss Elimination Method; Linear Equations; Matrix Method